2022
DOI: 10.21608/jesp.2022.235777
|View full text |Cite
|
Sign up to set email alerts
|

TORCH INFECTIONS, PATHOGENICITY & MORTALITY ASSESSMENTS

Abstract: A TORCH infection, also known as TORCH syndrome, is an infection of the developing fetus or newborn that can occur in utero, during delivery, or after birth. TORCH syndrome is a cluster of symptoms caused by congenital infection with toxoplasmosis, rubella, cytomegalovirus, Herpes simplex, and other organisms including syphilis, parvovirus, and Varicella zoster as well as Zika virus and others. TORCH syndrome is caused by in-utero infection with one of the TORCH agents, disrupting fetal development. Early diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…It has many common names (Blue gum, Camphor oil) and belongs to the family Myrtaceae, in a study conducted on humans, it was revealed that human facial demodicosis when treated with freshly prepared camphor oil with or without glycerol dilutions gave complete cure with concentrations of 100%, 75% and 50% respectively [24]. Revealed that camphor oil with or without glycerol dilutions completely cured zoonotic scabies with concentrations of 100%, 75% and 50% within 5-10 days [25].…”
Section: Eucalyptus Globulusmentioning
confidence: 99%
“…It has many common names (Blue gum, Camphor oil) and belongs to the family Myrtaceae, in a study conducted on humans, it was revealed that human facial demodicosis when treated with freshly prepared camphor oil with or without glycerol dilutions gave complete cure with concentrations of 100%, 75% and 50% respectively [24]. Revealed that camphor oil with or without glycerol dilutions completely cured zoonotic scabies with concentrations of 100%, 75% and 50% within 5-10 days [25].…”
Section: Eucalyptus Globulusmentioning
confidence: 99%
“…TORCH infections, which include toxoplasmosis, rubella, cytomegalovirus, and herpes virus, are known to cause significant prenatal, perinatal, and postnatal morbidity and mortality (Morsy et al, 2022). Infants may exhibit evidence of infection at birth, during infancy, or even years later.…”
Section: Introductionmentioning
confidence: 99%